Self-catalyzed tumor ferroptosis based on ferrocene conjugated reactive oxygen species generation and a responsive polymer. Issue 20 (17th February 2022) - Li, Jisi; Zong, Qingyu; Liu, Ye; Xiao, Xuan; Zhou, Jielian; Zhao, Zhongyi; Yuan, Youyong
Abstract : In this work, PTAF functions as a ferroptosis self-catalyst, through synergistic actions of self-catalyzed ˙OH accumulation and GPX4 indirect inactivation based on the ROS self-catalytic loop, effectively induced tumor ferroptosis. Abstract : In this work, we developed a ferroptosis self-catalyst, PTAF, exhibiting self-catalyzed ferroptosis for enhanced cancer therapy. Briefly, synergistic actions of self-catalyzed ˙OH accumulation and GPX4 indirect inactivation based on the establishment of the ROS self-catalytic loop effectively induced tumor ferroptosis, which provided a novel approach for enhanced tumor therapy.